A latent profile analysis of attributions for poverty: Identifying response patterns underlying people's willingness to help the poor. (October 2015) - Osborne, Danny; Weiner, Bernard
Highlights: We identify three distinct response profiles underlying attributions for poverty. Response profiles differed primarily along dimensions of locus and personal control. Conservatism and system justification predicted a Blaming response profile. Blaming profile predicted more anger, less sympathy, and less help for the poor. This is the first person-centered study of individual differences in attributions. Abstract: Attribution theory posits that poverty beliefs vary along the causal properties of locus, stability, personal control, and other control. The current paper extends this framework by using a latent profile analysis to identify the unique response patterns (latent profiles) that underlie these beliefs. Results indicated that participants ( N = 315) displayed one of three attributional profiles: Blaming (high internal locus; moderate stability; high personal control; high other control), Caring (low internal locus; moderate stability; low personal control; high other control), or Ambivalent (moderate across causal properties). Subsequent analyses showed that levels of conservatism and system justification positively correlated with membership in the Blaming (vs. Caring ) profile. In turn, belonging in the Blaming (vs. Caring ) profile predicted more anger, less sympathy, and less support for the poor. These findings advance attribution theory by taking a person -centered perspective and demonstrating that three distinct response patterns underlie individual differences in people's poverty beliefs.